Academia's class problem - Spiegel, Thomas J. (Frontiers in Research Metrics and Analytics, 2025)
The university has a problem with social class. Actually, it has two problems with class. The first one is that the university as an institution is still largely impervious to people from lower socio-economic backgrounds. In particular, people with middle and upper-middle-class backgrounds are overrepresented especially in very desirable tenured positions. This article offers a brief assessment of the problem, argues that more class diversity in academia is not only a matter of justice, but can also be epistemically beneficial, and finally formulates four desiderata for change.